Hak Nafkah Madhiyah Istri dalam Konsep Hukum Islam dan Implikasinya pada Putusan Pengadilan Agama - Muhammad Zhilal Haq; Muchlis Bahar; Zainal Azwar (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2024)
The Compilation of Islamic Law has stipulated that all forms of income obtained by a married couple will become joint property regardless of who made the effort to obtain the income. On the other hand, the Compilation of Islamic Law has also stipulated that the husband is obliged to bear the wife's maintenance. So the question arises from which assets the husband takes to fulfill this maintenance. From these two rules, it seems that there is a normative contradiction. This has implications for the decision of the Religious Court in the case of Nafkah Madhiyah. This qualitative research is conducted by studying the primary data sources of the decision documents of the Talu Religious Court Number 440/Pdt.G/2020/PA. Talu and the Padang Religious High Court Number 6/Pdt.G/2021/PTA.Pdg and the Compilation of Islamic Law (KHI). The focus of this research examines the judge's legal logic towards the fulfilment of the wife's right to nafkah madhiyah in a divorce case in the decision of the Talu Religious Court (PA) which was then appealed to the Padang Religious High Court (PTA). The results of this study indicate that the decision of the PTA Padang judge who rejected and cancelled the PA Talu judge's decision regarding nafkah madhiyah was more appropriate because the husband left the house with only the clothes he was wearing, while the wife could still fulfil her minimum living needs with the joint property left by her husband.